Chemical Composition of Rhizome Essential Oils of Amomum agastyamalayanum and Amomum newmanii from South India. Issue 3 (4th May 2018) - Kurup, Rajani; Thomas, V. P.; Jose, Judin; Dan, Mathew; Sabu, M.; Baby, Sabulal
Abstract: Chemical composition of rhizome essential oils of Amomum agastyamalayanum and A. newmanii from south India were analyzed by gas chromatographic techniques. Major constituents in A. agastyamalayanum rhizome oil were allo -aromadendrene (16.2 %), β-pinene (8.7 %) and (E)-caryophyllene (8.5 %). Santolina triene (42.2 %) and α-pinene (17.1 %) were the major constituents in A. newmanii rhizome oil. Monoterpene hydrocarbons, oxygenated monoterpenes, sesquiterpene hydrocarbons, oxygenated sesquiterpenes and other constituents in A. agastyamalayanum/A. newmanii rhizome oils were 16.3 %/73.7 %, 10.4 %/ 6.9 %, 48.8 %/13.1 %, 19.4 %/3.4 % and 2.1 %/1.0 %, respectively. This is the first chemical profiling study of these two endemic Amomum species.